Interactive E-Book Media Development for Enhancing Learning Outcomes in Akidah Akhlak Education in The 5.0 Era - Ery Dwika Andriani; Taufik Siraj (Journal of Islamic Education Students (JIES), 2025)
This study aims to develop an interactive e-book based on the Book Creator application to improve student learning outcomes in the subject of Akidah Akhlak in grade II at Siti Aminah Elementary School in Surabaya. The main problems are the suboptimal use of technology in learning and low student interest in learning. This study employs the Research and Development model ADDIE, which includes analysis, design, development, implementation, and evaluation. The instruments used include validation sheets, learning outcome tests, and practicality questionnaires. The validation results indicate that the interactive e-book is highly valid, with an average percentage exceeding 90%. The validation results showed that the e-book is highly valid with an average percentage 91,61%. The trial results indicated a significant improvement in learning outcomes with a high effectiveness category (N-Gain > 0.7). The e-book was also deemed highly practical by both teachers and students. In conclusion, the interactive e-book is effective and suitable for use in learning. It is recommended that teachers continue to innovate with interactive learning technology to enhance the quality of education.